OFFLINE PAYMENT VS ONLINE PAYMENT â CONSUMER INFLUENCING FACTORS IN UNIVERSITY STUDENTS - Pang, Ivana
The fourth industrial revolution has brought a rapid change towards human life in the world. The fourth industrial revolution has also digitized the world with the emergence of internet connection that is getting better and faster, and more sophisticated smartphone makes everything almost digital. This can cause lifestyle change becoming more digital, efficient, and practical. The digitization has an impact on all aspects of life, including financial aspects. Digitization in financial aspects itself is known as financial technology, a combination of financial and technological services. Many financial technology products that have facilitate people in organizing money, payment system, and also investment. One of financial technology product that developed by many companies and start-ups is e-wallet. E-wallet is financial technology in payment system based on server. This is possible because the high level of penetration and smartphone users makes Indonesia market feasible for e-wallet products. The emergence of e-wallet as payment instrument makes many people switch from cash to e-payment product moreover e-wallet service companies often give big discounts and promos to their users. Bank Indonesia as Indonesia central bank has also made a regulation related to these payment instruments. Seeing from above phenomena, the author wants to look in a more specific direction, with university students as the object of the research whether their lifestyles related to daily life activities are related to digital lifestyle, the preferred payment methods tend to be used today regarding the many payment instruments and whether the choice of using certain payment method is influenced by independent variables that found on the previous research. There are two payment methods that to be tested in this research, those are offline and online payment method. Offline payment instruments themselves consist of four payment instruments that are cash, debit card, credit card that using EDC machine, and e-money. Meanwhile for online payment methods consist of two payment instruments that are credit card with CVV code verification and e-wallet. This study uses questionnaire in data collection. From the analysis result from this study, it was found that average digital savviness index of respondents was quite high, but many respondents still tend to use offline payment especially cash, compared to online payments. This is predicted to have a significant effect of convenience and spending variables in choosing to use offline payment. This can be concluded from the results of the analysis using logistic regression. In the online payment method, the preferred payment instrument is e-wallet. The use of credit cards as a payment instrument is less preferred by university students. This may happen because of sources of income that mostly come from parents. Based on the analysis result, to further develop online payment, it can further enhance convenience level and added value on its use, because in its current stage, the choice in using online payment is significantly influenced by discount and surcharge variable.